2019
DOI: 10.3126/jpahs.v6i1.27087
|View full text |Cite
|
Sign up to set email alerts
|

Use of thromboprophylaxis for venous thromboembolism among patients admitted in medical ward

Abstract: Introductions: Studies have shown inadequate use of prophylaxis for venous thromboembolism (VTE) in hospital admitted medical patients. This study aims to evaluate the use of VTE prophylaxis in admitted medical patients in a tertiary care teaching hospital. Methods: This was a cross sectional observational study for three weeks from 19 March to 8 April 2017 in patients admitted in the medical ward of Patan Hospital, Patan Academy of Health Sciences, Lalitpur, Nepal. Patient charts were reviewed for appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…We found only one cross-sectional study from a teaching hospital in Nepal that reported 58% (40/69) of patients eligible for VTE chemoprophylaxis did not receive any prophylaxis. 14 …”
Section: Discussionmentioning
confidence: 99%
“…We found only one cross-sectional study from a teaching hospital in Nepal that reported 58% (40/69) of patients eligible for VTE chemoprophylaxis did not receive any prophylaxis. 14 …”
Section: Discussionmentioning
confidence: 99%